Análise da paisagem no município de Palmeirante, Tocantins (período 2009-2019) - LIMA, Thalia da Silva (Universidade Federal do Tocantins, 2023)
This research aimed to evaluate the temporal dynamics of the landscape in the municipality of Palmeirante/TO, aiming to generate subsidies for public management and environmental conservation, with a time frame from 2009 to 2019, in order to understand the various transformations that occurred in the landscape, especially in native vegetation for the implantation of livestock and agriculture. As for the methodological procedures, four steps were carried out: 1) bibliographic survey on the subject; 2) survey of secondary data on the site of the National Institute for Space Research (INPE) and the Brazilian Institute of Geography and Statistics (IBGE); 3) elaboration of maps in Quantum Giz software, version 3.18 and; 4) data analysis. The results show that the livestock class has the highest rate of land occupation in the study area, in the period analyzed, increasing its percentage to 83.56% in 2019, while in the same period the savannas had a decline in their areas from 16.64% to 12.02%. Another point to be highlighted in the study is the growth of conventional agriculture, from 0.33% in 2009 to 2.96% in 2019. Adding livestock and conventional agriculture, we have a percentage of 86.52% of the area occupied and consequently impacted, which causes destruction of regional ecosystems, deterioration of water resources, threats to endemic species and loss of biodiversity. It is concluded that mitigating measures are needed for the conservation of biodiversity and the implementation of environmental policies for the conservation of forest fragments that still exist in the analyzed area